Performance analysis of dual non-orthogonal multiple access technology in the Internet of things - Dongbo LI; Min JIA; Qing GUO; Xuemai GU; Xiaofeng LIU (物联网学报)
With the rapid development of many technologies such as smart city,artificial intelligence and edge computing,the future Internet of things will face the problems of massive terminal access and spectrum resource constraints.A dual non-orthogonal multiple access (D-NOMA) technology based on high spectral efficiency secure access (HSESA) was proposed,which combined non-orthogonal access in the code domain and non-orthogonal multiplexing in the frequency domain,and had good spectral efficiency performance.The sender and receiver were optimized,and multiple users were mapped directly to the overlapping subcarriers through the sparse codebook.The performance analysis under the Rician channel shows that D-NOMA has better bit error rate performance than HSESA.